Variasi Konsonan Bahasa Jawa pada Masyarakat Kelas Bawah di Daerah Istimewa Yogyakarta - Zultiyanti Zulti (Universitas Muhammadiyah Kotabumi, 2022)
This study aims to determine the variation of Javanese consonants in the lower-class community in RT 34-35 Giwangan Village, Umbulharjo District, Special Region of Yogyakarta. This type of research is a case study, data obtained utilizing interviews and literature study. The study results indicate that there are variations in consonants that occur in the lower society. The consonant variations are a form of neutral in the word pairs /b/ and /p/, which occurs in the word